The lilac house - Josselsohn, Barbara Solomon (Forever, 2021)
"Lilac House has always been a source of comfort for Anna Harris. Though things will never be the same since her husband's death ... soon she's caught up in the rhythm of small-town life ... Then she meets Aidan ... But Aidan's ... hiding a secret about why he came to Lake Summers ... Just as Lilac House starts to feel like home, Anna learns something devastating about her husband's death that will make her question everything she's always known to be true"--